HARGA DAN KEBERAGAMAN PRODUK SERTA PENGARUHNYA TERHADAP LOYALITAS PELANGGAN RESTORAN - Ella Anastasya Sinambela; Rahayu Mardikaningsih (Universitas Mahendradatta, 2022)
The restaurant business is one of the most competitive businesses inthe industry. The strategic step of each restaurant is to determine whichcompetitive variables can attract new customers and keep existing customersvery important to managing a successful restaurant. Various offers in therestaurant industry cause the perpetrators to try to get loyalty from theircustomers. This study aims to analyze the effect of price and product variant oncustomer loyalty. The survey was conducted on 110 customers using accidentialsampling techniques. Multiple linear regression analysis using SPSS 25 forWindows software is used as an analysis tool for data processing. The resultsshowed that the price and product variant had a significant effect on customerloyalty partially or simultaneously.